Membangun Usaha Berdasarkan Kearifan Lokal dalam Rangka Ketahanan Ekonomi di Krasaan, Jogotirto, Berbah, Sleman, Yogyakarta - Maelana, Herman Wahyu Dwi; Himawan Agung Nugroho; Susatyo Herlambang; Luluk Priyanti; Saimin (LPPM Akademi Manajemen Administrasi Yogyakarta, 2026)
This Community Service Program (PkM) aims to enhance entrepreneurial motivation, business management skills, and collaboration among Micro, Small, and Medium Enterprises (MSMEs), Women Farmers’ Groups (KWT), and youth in Krasaan Hamlet, Jogotirto, Berbah, Sleman, Yogyakarta. The main problems faced by the community include low entrepreneurial motivation, weak financial management, and limited synergy among local potentials. The methods employed consisted of lectures, counseling, and interactive discussions. The results of the program indicate an increase in participants’ understanding of the importance of businesses based on local wisdom, the separation of personal and business finances, and collaborative strategies. This program provides tangible contributions to strengthening the economic resilience of families and communities. Keywords: MSMEs, local wisdom, entrepreneurship, financial management, economic resilience